The Clinical Learning Environment, Supervision and the Nurse Teacher Evaluation Scale: Turkish Version - Iyigun, Emine; Tastan, Sevinc; Ayhan, Hatice; Pazar, Berrin; Tekin, Yasemin Eda; Coskun, Halise; Saarikoski, Mikko (Wiley, 2020)
Aim The aim of this study is to adapt the Clinical Learning Environment, Supervision and Nurse Teacher Evaluation Scale to the Turkish language and culture. Methods This psychometric test was conducted in a nursing school in Ankara, Turkey, from April to June 2014. Convenience sampling was used. The sample of this study was 190 third- and fourth-year nursing students. The items of the scale were evaluated by Pearson correlation coefficient for correlation-based item analysis. Cronbach's alpha, test and retest analysis were used to measure reliability. Exploratory factor analysis and correlation analysis were performed to determine validity. Principal component analysis was used to analyze factor. Results The subscales' Cronbach's alpha values were varied between .760 and .933. A positive relationship was found between tests and retests points of the subscales (P < .05). Five factors were identified in the exploratory factor analysis. There was a meaningful correlation between subscale points of the Clinical Learning Environment, Supervision and Nurse Teacher Evaluation Scale and the Clinical Learning Environment Scale (P < .05). Conclusion The Turkish version of the Clinical Learning Environment, Supervision and Nurse Teacher Evaluation Scale was validated and a reliable measurement tool. It can be used to evaluate clinical nursing education in Turkey.
Keywords: clinical education; instrument development; learning environment; nurse teachers; Turkey